2019
DOI: 10.1039/c8ra10247c
|View full text |Cite
|
Sign up to set email alerts
|

Metal-mediated synthesis of pyrrolines

Abstract: The five-membered, nitrogen-containing pyrroline ring is a privileged structure. Pyrrolines—the dihydro derivatives of pyrroles—have three structural isomer classes: 1-, 2- and 3-pyrrolines. A review on metal-mediated synthesis of the three classes of pyrrolines is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 194 publications
0
17
0
Order By: Relevance
“…Representative examples of the major classes of biologically relevant scaffolds presented in the minireview. [30][31][32][33]…”
Section: Figurementioning
confidence: 99%
“…Representative examples of the major classes of biologically relevant scaffolds presented in the minireview. [30][31][32][33]…”
Section: Figurementioning
confidence: 99%
“…[1] Among the known nitrogen-containing heterocycles, pyrrolines are one of the most important classes of azaheterocycles found in a variety of natural products and bioactive molecules. [2] Furthermore, the heteroatom substituted pyrrolines have exhibited a number of interesting chemical and biological properties. [3] Literature survey has revealed that among numerous protocols to access pyrroline derivatives, [2a] (3 + 2)-cycloaddition of donor-acceptor cyclopropanes (DACs) are few.…”
Section: Introductionmentioning
confidence: 99%
“…From the marine alkaloid group with the tri-and tetrasubstituted pyrrole ring, lamellarins O, Q, R for their anticancer activity [5] and storniamids A-D for antibacterial activity [3] stand out (Figure 2). Additionally, pyrroles are useful building blocks [18][19][20][21] in the design and synthesis of naturally occurring compounds, functionalized materials, and new bioactive condensed heterocycles, and as a consequence, the interesting synthetic aspects and applications of the compounds possessing the pyrrole core have been reviewed [9][10][11][12][13]18,[22][23][24][25][26][27][28][29]. The 1,4-dihydropyridine (DHP) class is frequently the first choice of drug used in the treatment of hypertension [30] and angina [31].…”
Section: Introductionmentioning
confidence: 99%